Life Challenges of life, reptiles and amphibians, mammals. (DVD). - Attenborough, David (BBC Worldwide Ltd. Program, 2010)
Challenges of life : In nature, living long enough to breed is a monumental struggle. Many animals and plants go to extremes to give themselves a chance. Uniquely, three brother cheetahs band together to bring down a huge ostrich. Aerial photography reveals how bottlenosed dolphins trap fish in a ring of mud, and time-lapse camerasw show how the Venus flytrap ensnares insect victims. The strwberry frog carries a tadpole high into a tree and drops it in a water-filled bromeliad. The frog must climb bacj from the ground everyday to feed it. Fledging chinstrap penguins undertake a heroic and tragic journey through the broken ice to get out to sea. Many can barely swim.